TOPICAL ISSUES OF IDEOLOGICAL AND IDEOLOGICAL PRESERVATION OF THE MINDS AND HEARTS OF YOUNG PEOPLE FROM INFORMATION ATTACKS ON THE INTERNET (American Journal of Interdisciplinary Research and Development, 2023)
In today's, efforts to conquer the human mind have become increasingly powerful as a result of the transformation of information on the internet into a powerful weapon. In turn, it should be especially recognized that information attacks on the Internet act as the main factor in ideological and ideological influence. In this regard, the further formation of ideological immunity against various information threats in our youth is becoming relevant. Consequently, the education of our youth on the basis of strict faith and faith in the future of our society is one of the requirements of the time.